DIGITAL MULTICULTURAL LEARNING TRANSFORMATION THROUGH THE ONLINE PMM PROGRAM - Kamil; Suci Rahmadani; Latifah Hannum; Nabila Dwi Alhusna; Nur Innayah; Gilang Purnama; Ulul Amri (International Journal of Society and Law, 2025)
The transformation of education through digital platforms has significantly impacted the implementation of multicultural learning in Indonesia, especially in the context of the Independent Student Exchange Program (PMM) under the Merdeka Belajar Kampus Merdeka (MBKM) policy. Initially designed as an offline exchange program, PMM shifted to an online format during the COVID-19 pandemic to maintain the program's core values of diversity, tolerance, and national identity. This research aims to explore the role and impact of online PMM in fostering digital multicultural learning, focusing on its influence on students' national identity, tolerance, and cross-cultural empathy.Through a qualitative descriptive approach, data was collected from academic journals, government documents, and other scholarly sources. The findings suggest that online PMM has successfully improved students' multicultural competencies, including cultural sensitivity, communication skills, and empathy, despite the challenges posed by digital divides and intercultural communication barriers. The Nusantara Module, a key component of the PMM, has played a vital role in encouraging reflection on national identity and promoting an understanding of Indonesia’s cultural diversity.However, challenges such as limited access to digital infrastructure, cultural communication gaps, and the lack of emotional interaction in online settings need to be addressed for the program to reach its full potential. This paper highlights the importance of improving digital infrastructure, strengthening the capacity of facilitators, and innovating the Nusantara Module to enhance the effectiveness of digital multicultural learning. The research concludes by offering policy recommendations for improving the sustainability and impact of online PMM in the future, thus contributing to national integration and the values of Bhinneka Tunggal Ika (Unity in Diversity).